PENGEMBANGAN SUPER VOUCHER MOTIVATION PADA MATERI VIRUS UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI SISWA KELAS X - LUKITASARI, NUNGKI (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Young scientist (young researchers) have a sense of curiosity (curiousity) high. The reality on the ground there are still many children that high curiosity was not supported by a condition that can give them the opportunity to be more developed. Though they are in need of understanding the concepts related to everyday life. As a result, the motivation to study hard to be grown and learned patterns they tend to memorize and mechanistic. This study aims to develop learning aids super voucher motivation, describes eligibility super voucher, analyzes super voucher, student activities and student learning outcomes of the super voucher motivation on viral material. This research is a development that aims to discover and develop a new method or the existing ones in order to improve and development so as to obtain better results, effective than before. Development research trial was conducted on 19-20 September 2012. Objectives of this research is the development of the feasibility study aids such as super card vouchers motivation will be tested in class X SMAN 4 Sidoarjo, amounting to 33 students. The research instrument used in data collection are pieces of the validation, observations of student activity sheets. The analysis used is quantitative descriptive analysis. The results of the analysis of the data obtained, the average percentage of the feasibility of super voucher of 84.3%, an average gain more green cards in the amount of 60.56% of the total student acquisition orange card in the amount of 15.15%, which means less while for the purple card for 45.45% of the total students. Analysis of student learning outcomes indicated by the classical mastery learning is as much as 84.4%. Student activity data in the study group after acquired averaged as much as 87.4%. So it can be concluded that the learning aids in the form of super voucher motivation feasible for use in learning virusdan create a pleasant atmosphere for learning. Keywords: super voucher motivation, motivation, virus